The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s00464-001-9145-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic splenectomy using ligasure

Abstract: The use of Ligasure, associated with the lateral position, results in a gain of time and safety. Furthermore, the average intraoperative bleeding of this series is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 22 publications
2
84
1
5
Order By: Relevance
“…11 Recently, LS has been increasingly indicated for splenomegaly, owing to advances in laparoscopic devices such as harmonic scalpel, ligasure vessel sealing system and endoscopic vascular stapler, and improvements in surgical procedures. [12][13][14][15][16] It has been reported that LS was feasible and is associated with a lower morbidity and shorter hospital stay than OS in patients with splenomegaly. 17,18 The indications for LS and LS with devascularization (LSD) have also been extended to patients with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, LS has been increasingly indicated for splenomegaly, owing to advances in laparoscopic devices such as harmonic scalpel, ligasure vessel sealing system and endoscopic vascular stapler, and improvements in surgical procedures. [12][13][14][15][16] It has been reported that LS was feasible and is associated with a lower morbidity and shorter hospital stay than OS in patients with splenomegaly. 17,18 The indications for LS and LS with devascularization (LSD) have also been extended to patients with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Vessels sealed in this manner have demonstrated clinically equivalent bursting pressures when compared with vascular staples, titanium clips, and sutures, and significantly higher pressures when compared with the harmonic scalpel in vessels in 4-7 milimeter (mm) diameter range. [25][26][27] Romano and coworkers [28] reported success using the LigaSure Vessel Sealing System (Valleylab) in performing laparoscopic splenectomy. Similarly head and neck surgeons have demonstrated a reduced operative time and blood loss during thyroidectomy using the ligasure vessel sealing system.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] As mentioned above, in a series of LA in which the LigaSure ® device was used the reported operation times were between 57 to 123 minutes and mean sizes of the adrenal masses were between 40 to 62 mm. [13][14][15] In the present study, the mean operation time and mean size of the adrenal masses in the LigaSure ® device group were 90.2 (range; 50 to 150) minutes and 37.2 (range; 15 to 72) mm, respectively.…”
Section: Discussionmentioning
confidence: 99%